Diagnostic Value of Rheumatoid Factor and Anti-CCP in Seropositive and Seronegative Rheumatoid arthritis patients at a Tertiary Hospital in Tamil Nadu - S, Vinithra; K, Sethumadhavan; K, Bhaskaran; J, Pradeep; M, Suresh; SM, Nachammai (Journal of Neonatal Surgery, 2025)
Rheumatoid Arthritis (RA) is not an uncommon disease and its rate of prevalence is estimated about 1- 1.5% across the globe. It is a non-organ specific autoimmune disease which is categorized by systemic, chronic and symmetric inflammation involving multiple joints, predominantly the small joints. The aim of this study is to evaluate the diagnostic value of Anti-CCP autoantibodies with the standard rheumatoid factor (RF) among seropositive and negative patients attending a tertiary care hospital. This is a cross sectional study was conducted in a tertiary care hospital in and around Coimbatore district. The total study population was categorized into two groups 80 RF positive and 80 RF negative for the performance of anti-CCP ELISA. The age of the RA positive patients ranges from 28 to 83 years and for negative patients about 18 to 75 years old. Among the RA-positive group, 19 patients (23.7%) were tested positive for anti-CCP antibodies, while the remaining 61 (76.3%) were negative. In the RA-negative group, 15 patients (18.7%) were anti-CCP positive, whereas 65 (81.3%) tested negative. Rheumatoid factor is the significant diagnostic marker for RA till the discovery of Anti –CCP autoantibodies. The study concludes that anticitrullinated protein antibodies are more sensitive than RF antibodies. Anti-CCP is considered to be early diagnostic marker for the diagnosis of RA than other serological tests.